2020
DOI: 10.1002/pros.24038
|View full text |Cite
|
Sign up to set email alerts
|

Reduced KLK2 expression is a strong and independent predictor of poor prognosis in ERG‐negative prostate cancer

Abstract: Background: Kallikrein-related peptidase 2 (KLK2)-like KLK3 (prostate-specific antigen [PSA])-belongs to the highly conserved serine proteases of the glandular kallikrein protein family (KLK family). Studies suggested that measurement of KLK2 serum levels advanced the predictive accuracy of PSA testing in prostate cancer. Methods: To clarify the potential utility of KLK2 as a prognostic tissue biomarker, KLK2 expression was analyzed by immunohistochemistry in more than 12 000 prostate cancers. Results: Normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
0
16
2
Order By: Relevance
“…FOXA1, KLK2, and TMPRSS2 gene expressions were all significantly inhibited by α-mangostin, confirming that nuclear translocation of AR is occurring and that PCa cell proliferation is being affected ( Figure 1 E). KLK2, one of the genes whose expression was most significantly decreased by α-mangostin, plays a role in carcinogenesis and tumor metastasis, and it was recently revealed that high KLK2 expression correlates with PCa severity and aggressiveness [ 40 , 41 ]. This has been shown to be especially true in TMPRSS2-ERG negative PCa; TMPRSS2 is well characterized as an AR-responsive and prostate-specific gene that can mutate and form TMPRSS2-ERG, one of the most common mutations in PCa that can be used as a prognostic marker [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…FOXA1, KLK2, and TMPRSS2 gene expressions were all significantly inhibited by α-mangostin, confirming that nuclear translocation of AR is occurring and that PCa cell proliferation is being affected ( Figure 1 E). KLK2, one of the genes whose expression was most significantly decreased by α-mangostin, plays a role in carcinogenesis and tumor metastasis, and it was recently revealed that high KLK2 expression correlates with PCa severity and aggressiveness [ 40 , 41 ]. This has been shown to be especially true in TMPRSS2-ERG negative PCa; TMPRSS2 is well characterized as an AR-responsive and prostate-specific gene that can mutate and form TMPRSS2-ERG, one of the most common mutations in PCa that can be used as a prognostic marker [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression of KLK family members 5–8 (KLK5–8) was associated with a more aggressive clinicopathologic phenotype and worse prognosis in endometrial cancer (EC) patients [ 39 ]. In contrast, low expression of KLK2 was associated with advanced tumour stage, more lymph node metastasis, increased cell proliferation, positive resection margin, and early PSA recurrence in prostate cancer [ 40 ]. However, the role of KLKs in CRC remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64][65] KLK2 staining also appears to be reduced in advanced tumors, and, interestingly, loss of staining is associated with TMPRSS2:ERG gene fusion, which in turn is associated with prostate cancer development. 66,67 However, increased staining of KLK2 in prostate cancer tissue has also been reported. 68 The expression of several other KLKs, including KLK4 and KLK14, is also changed in prostate cancer.…”
Section: Proteases In Prostate Cancermentioning
confidence: 99%
“…However, KLK3 expression tends to be lower in prostate cancer tissue than in the benign prostate and reduced KLK3 immunostaining is associated with poor prognosis 62–65 . KLK2 staining also appears to be reduced in advanced tumors, and, interestingly, loss of staining is associated with TMPRSS2:ERG gene fusion, which in turn is associated with prostate cancer development 66,67 . However, increased staining of KLK2 in prostate cancer tissue has also been reported 68 .…”
Section: Proteases In Prostate Cancermentioning
confidence: 99%